The antimicrobial cyclic peptide B2 combats multidrug resistant Acinetobacter baumannii infection. (17th March 2022) - He, Qingxiu; Zhao, Linan; Li, Guangping; Shen, Yan; Hu, Yong; Wang, Yuanqiang
Abstract : In silico methods were employed for the development of antimicrobial peptides against MDR A. baumannii by binding to BamA. Abstract : There is a crucial need for novel antibiotics against multi-drug resistant Gram-negative pathogens. BamA is an outer membrane β-barrel protein that is required for the folding and insertion of β-barrel proteins into the outer membrane. Targeting BamA has been demonstrated as a new avenue for antibiotic discovery. Here, we screened a set of cyclic peptides against BamA from our in-house peptide library by molecular docking with high-precision. All these screened cyclic peptides exhibited activity against Staphylococcus aureus, Escherichia coli, Acinetobacter baumannii and multidrug-resistant Acinetobacter baumannii (MDR A. baumannii ). Notably, the lead peptide B2 (cyclo-RRWWRRW) exhibited potent activity against both the standard and clinical MDR A. baumannii strains. Peptide B2 killed A. baumannii by permeabilizing the bacterial membrane and showed little hemolysis. Moreover, peptide B2 showed significant therapeutic effects on lung infections in mice induced by the infection of clinical MDR A. baumannii . Furthermore, we explored the binding mode of peptide B2 complexed with BamA by molecular simulation, and the key residues were identified by their binding energy contributions, which might be used to guide targeted candidate discovery of novel antimicrobial agents. This study provides a new strategy for the development of antimicrobial peptides to address life-threatening infections by Gram-negative pathogens.